Pertumbuhan Usus dan Performa Itik Tegal Akibat Diberi Sinbiotik (Campuran Lactobacillus casei dan Glukomanan) - Istna Mangisah; Nyoman Suthama; Raka Panji Pratama (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Mangisah I, Suthama N, Pratama RP. 2020. Intestinal growth and performance of tegal ducks due to administration of sinbiotics (Mixture of Lactobacillus casei and Glucomannan). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to examine the effect of synbiotic levels (a combination of L.casei and glucomannan from porang tuber extract) and the duration of administration on the growth of the digestive tract and the performance of Tegal ducks. A total of 180 male Tegal ducks, 2 days old with an average body weight of 42,33±2,54 were used in this study. The treatment rations were prepared with a metabolic energy of 3000 kcal/kg and crude protein 18%. The research was arranged in a factorial completely randomized design, with 2 factors. The first factor was the synbiotic level (1 and 2%), while the second factor was the duration of synbiotic administration (2,3 and 4 weeks). The collected data were analyzed for variance and continued with the Duncan multiple region test. The results showed that there was an interaction between the synbiotic level and the duration of synbiotic administration on the length of the duodenum, jejenum and ileum as well as the final body weight of Tegal ducks. The conclusion was that 2% of synbiotics for 4 weeks increased intestinal growth and body weight of Tegal ducks.